Economic Development of Mysore 1956-69 - Planning Commission (Planning Commission, 1970)
The present enlarged State of Mysore came into existence on 1st November, 1956 under the States Reorganisation Act. The erstwhile State of Mysore came into being in 1799 A.D. after the Fourth Mysore War and the extent of territory included in it remained unchanged up to 1950. In 1950, there was an exchange of enclave areas between the State of Mysore and the then Province of Madras under the Provinces and States (Absorption of Enclaves) Order, 1950 and these exchanges resulted in an increase in the area of the State from 76,296 sq. kilometres (29,458 sq. miles) to 76,376 sq. kilometres (29,489 sq . miles). The next change in the area of the State was in October, 1953 when the Bellary district of Madras State excluding the taluks of Adoni, Alur and Rayadurg was transferred to the State of Mysore under the Andhra State Act, 1953.
Bureau of Economics and Statistics Government of Mysore